Comprehensive Analysis of the Oncogenic, Genomic Alteration, and Immunological Landscape of Cation-Chloride Cotransporters in Pan-Cancer - Wang, Jie; Liu, Wangrui; Xu, Wenhao; Yang, Baofeng; Cui, Mingzhu; Li, Zhen; Zhang, Hailiang; Jin, Chuntao; Xue, Huanzhou; Zhang, Jiaqiang (Frontiers in Oncology, 2022)
Background Assessing the phenotypic diversity underlying tumor progression requires the identification of variations in the respective molecular interaction in the tumor microenvironment (TME). Despite emerging studies focusing on the association between cation-chloride cotransporters (CCCs) and carcinogenesis, direct evidence that CCCs (KCC2 and NKCC1) mediate tumor progression in pan-cancer remains unclear. Methods We conducted a comprehensive assessment of the expression, DNA variation profiles, and prognostic and immunologic implications of CCCs based on a large-scale pan-cancer population, including 10,967 cancer patients from the Cancer Genome Atlas, 9,162 cancer patients from Genomics Expression Omnibus, 48,834 cancer patients from 188 independent studies, and 356 cancer patients from three real-world cohorts. Results In this study, we first found that CCCs were highly expressed in most tumors, and prominently associated with prognosis. Kaplan–Meier analysis and Cox regression analysis revealed that KCC2 and NKCC1 significantly predicted survival for patients with pan-cancer, suggesting that CCCs have inconsistent tumorigenesis regulatory mechanisms in cancers. Next, we examined the DNA variation landscape of KCC2 and NKCC1 and their prognostic implications in pan-cancer. The results demonstrated that UCEC patients with somatic copy number variation (CNV) of NKCC1 received significantly better outcomes (p < 0.05). Besides emphasizing the clinical implications of CNV of CCCs for cancer patients, we found that NKCC1MUT could prominently prolong progression-free survival (p = 2.59e-04), disease-specific survival (p = 0.019), and overall survival (p = 0.034) compared with NKCC1WT cancer patients possibly via regulation of cell proliferation and oncogenic stress pathways. Additionally, KCC2 positively correlated with the levels of tumor-infiltrating macrophages and CD4+ T cells, but NKCC1 showed a significantly widely negative association with tumor-infiltrated lymphocytes, suggesting an immune-excluded TME in cancers. Similarly, expression of KCC2, rather than NKCC1, was positively correlated with the immune checkpoint molecules, indicating its role as an immune regulator in a wide variety of cancers. Finally, to verify our hypothesis and altered expression of CCCs, we performed IHC analysis and revealed the staining distribution in tumor and adjacent normal tissues of glioma, clear cell renal cell carcinoma, papillary cell renal cell carcinoma, and hepatocellular and breast cancer from three real-world cohorts, and validated prominently prognostic implications of CCCs in patients with clear cell renal cell carcinoma. Conclusion This study first comprehensively investigated the molecular and clinical role of CCCs, and illustrated the significant association among KCC2/NKCC1 expression, DNA variation profiles prognosis, and TME of pan-cancer. The pan-cancer findings provided an in-depth understanding of potential oncogenic and immunologic of differential expression and DNA alteration of KCC2/NKCC1 cancers.